Role of Adult Asthma Education in Improving Asthma Control and Reducing Emergency Room Utilization and Hospital Admissions in an Inner City Hospital - Rashmi Mishra; Muhammad Kashif; Sindhaghatta Venkatram; Teresa George; Kristina Luo; Gilda Diaz-Fuentes (Canadian Respiratory Journal)
Objective. Asthma education programs have been shown to decrease healthcare utilization and improve disease control and management. The purpose of our study was to evaluate the impact of an outpatient adult asthma education program in an inner city hospital caring for patients with low socioeconomic and educational status. Methods. An asthma education program was implemented in September 2014. Patients who received education from September 2014 to July 2015 were evaluated. Outcomes were compared for the same group of patients before and after education. Primary outcomes were emergency room (ER) visits and hospital admissions. Secondary outcomes were change in Asthma Control Test (ACT) score and number of pulmonary clinic visits. Results. Asthma education significantly decreased number of patients requiring ER visits and hospital admissions (p = 0.0005 and p = 0.0015, resp.). Asthma control as per ACT score ≥ 20 improved with education (p = 0.0001) with an increase in clinic visits (p = 0.0185). Conclusions. Our study suggests that implementation of a structured asthma education program in an inner city community hospital has a positive impact on reduction of ER visits and hospital admissions with improvement in asthma control. Institutional Review Board Clinical Study registration number is 01081507.